Imprescriptibilidad para perseguir y proseguir en los delitos de violación sexual - Calvas Torres, Eduardo Luis (2014)
The general requirement is a legal institution, which over time has the effect of consolidating the factual situations, allowing the extinction of the rights or the acquisition of things outside. In criminal law the requirement to extinction, both action (prescription of prosecution); and penalty (prescription of punishment). The rape is a sexual assault that occurs when a person has sexual access to another through the use of physical or psychological violence or by using mechanisms that override the consent of the offended. The violation is of vital importance in the global legal scheme, being considered a felony because undertakes a number of wards as part of the fundamental rights of human beings. The Constitution of the Republic of Ecuador, guarantees people the right to humane treatment that includes physical, mental, moral and sexual integrity. The Penal Code, Article 101, states that the exercise of the right prescription sets, the following rules shall be observed: Both offenses against public order as in crimes of private action will be distinguished above all if he committed the crime, has been started or not prosecution. Except for cases of applicability of actions and penalties provided for in the last paragraph of paragraph 2 of Article 23 (80) and the second subparagraph of Article 121 (233) of the Constitution of the Republic, on the other crimes punishable by imprisonment, the exercise of public action is, in the absence of prosecution, the action to prosecute prescribe in ten years; case of offenses punishable with rigorous imprisonment particular, action to continue them prescribe in fifteen years. In the crimes of public action, if trial started before those deadlines are met, the action to continue the cause prescribed by the same date, from the date of autocabeza process. The penalty for the crime of rape referred to in Article 513, according to each case can be especially rigorous imprisonment and extraordinary long-term imprisonment, ie the time to pursue and continue will be 10 and 15 years respectively. For centuries, sexual violence in conflict is tacitly accepted as inevitable. A United Nations report of 1998 on sexual violence and armed conflict, said that it should be recognized sexual violence as an international crime, in this sense, the present research work arises from the need that our legal system conforms with the considerations internationally is driving, in order to establish that crimes of sexual violation, action to pursue to continue to be imprescriptible.